Analisis Evaluasi Diri Guru sebagai Alat untuk Meningkatkan Kompetensi Profesional di SMA Negeri 1 Maumere - Trisnawati Bura; Fathia Aulia Muthmaina; Elisabeth Henderika Dua Neang; Yosefa De Ancieta; Anastasia Yunianti (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Self-evaluation is an important instrument in teacher professional development, as it can help identify strengths and weaknesses in learning practices. This study aims to describe in depth the practice of teacher self-evaluation, the supporting and inhibiting factors, and its impact on teacher professional development in the school environment. This study used a descriptive qualitative approach with a case study method focused on a teacher at SMA Negeri 1 Maumere. Data collection techniques were conducted through an open-ended questionnaire designed to explore teachers' understanding of self-evaluation practices, as well as observations of lesson planning documents. The results showed that the teachers who were the subjects of the study had fairly good lesson planning and demonstrated a commitment to improving the quality of teaching. However, several challenges remained, such as difficulties in optimally adapting the curriculum to student needs and limitations in developing and implementing relevant learning evaluation instruments. Furthermore, the utilization of evaluation results for learning improvement has not been optimal. Although teachers have been active in Classroom Action Research (CAR), the integration of self-evaluation results into learning innovations still requires strengthening. Factors supporting self-evaluation include teachers' intrinsic motivation to develop, principal support, and relevant training. Meanwhile, inhibiting factors include time constraints, administrative burdens, and the lack of reflective forums at the school level. This study confirms that self-evaluation conducted in a structured and reflective manner can play a significant role in improving teachers' professional competence and the quality of learning in schools.